2012
DOI: 10.1007/s11664-012-2270-8
|View full text |Cite
|
Sign up to set email alerts
|

Realization of the Switching Mechanism in Resistance Random Access Memory™ Devices: Structural and Electronic Properties Affecting Electron Conductivity in a Hafnium Oxide–Electrode System Through First-Principles Calculations

Abstract: The resistance random access memory (RRAMä) device, with its electrically induced nanoscale resistive switching capacity, has attracted considerable attention as a future nonvolatile memory device. Here, we propose a mechanism of switching based on an oxygen vacancy migration-driven change in the electronic properties of the transition-metal oxide film stimulated by set pulse voltages. We used density functional theory-based calculations to account for the effect of oxygen vacancies and their migration on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Here we should note that in Ref. [25] the conductive path in HfO 2 ReRAM was attributed to negatively charged oxygen vacancy chains, which are responsible for the formation of partially occupied defect states in the electronic density of states. It was shown that the electroforming process is initiated by a supply of neutral oxygen Frenkel defect pairs, and the accumulation of the oxygen vacancies results in the formation of local metallic suboxide phases, HfO x , which remain conductive even as ultranarrow filaments in the insulating matrix.…”
Section: A Energetics and Structure Of Metastable Hfo X Phasesmentioning
confidence: 81%
See 4 more Smart Citations
“…Here we should note that in Ref. [25] the conductive path in HfO 2 ReRAM was attributed to negatively charged oxygen vacancy chains, which are responsible for the formation of partially occupied defect states in the electronic density of states. It was shown that the electroforming process is initiated by a supply of neutral oxygen Frenkel defect pairs, and the accumulation of the oxygen vacancies results in the formation of local metallic suboxide phases, HfO x , which remain conductive even as ultranarrow filaments in the insulating matrix.…”
Section: A Energetics and Structure Of Metastable Hfo X Phasesmentioning
confidence: 81%
“…Here we note that the relative position of I bam-Hf 2 O 3 and P4m2-Hf 2 O 3 strongly depends on the choice of U . However, for all reasonable values [25] of U eff above ∼3 eV with the PBE functional (and ∼4 eV for PBEsol), the Ibam-Hf 2 O 3 phase has a lower energy than the P4m2-Hf 2 O 3 one. For U eff 3 eV (or U eff 4 eV for PBEsol) including the calculations performed with U eff = 0 eV, P4m2-Hf 2 O 3 has the lowest energy, as reported previously [30,31].…”
Section: A Energetics and Structure Of Metastable Hfo X Phasesmentioning
confidence: 94%
See 3 more Smart Citations